2000
DOI: 10.1034/j.1399-3054.2000.1100419.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper effect on the protein composition of photosystem II

Abstract: We provide data from in vitro experiment on the polypeptide composition, photosynthetic electron transport and oxygen evolution activity of intact photosystem II (PSII) preparations under Cu(II) toxicity conditions. Low Cu(II) concentrations (Cu(II) per PSII reaction centre unit < 230) that caused around 50% inhibition of variable chlorophyll a fluorescence and oxygen evolution activity did not affect the polypeptide composition of PSII. However, the extrinsic proteins of 33, 24 and 17 kDa of the oxygen-evolvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Photosynthetic processes in algae are strongly affected by Cu concentration (Yruela et al, 1996(Yruela et al, , 2000. A strong decrease in chlorophyll fluorescence of plants is associated with chlorophyll damage when exposed to copper (Ciscato et al, 1997;Küpper et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthetic processes in algae are strongly affected by Cu concentration (Yruela et al, 1996(Yruela et al, , 2000. A strong decrease in chlorophyll fluorescence of plants is associated with chlorophyll damage when exposed to copper (Ciscato et al, 1997;Küpper et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Various sources of Cu, including industrial and domestic wastes, and copper-based pesticides have contributed to an increase of Cu concentration in aquatic environments (Ho, 1987;Nor, 1987;Correa et al, 1996), with many negative effects on algae being reported at high Cu concentrations (Harrison et al, 1977;Pandey and Singh, 1992;Kenefick et al, 1993;Okamoto and Colepicolo, 1998;Yruela et al, 2000;Bossuyt and Janssen, 2004;Nielsen and Nielsen, 2005). In response to the stress of high Cu concentration, algae display a defense mechanism, including the changed activity of superoxide dismutase (SOD) (Okamoto and Colepicolo, 1998), protein composition (Yruela et al, 2000), and so on. Treatment levels reported in the literature are generally in the range of 0.025e1 mg l À1 of Cu 2þ to control the nuisance algae blooms (McKnight et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrences of Cu-, Ni-and Zn-sulphidic ores (Barrie et al 2008), and their mining and processing have often resulted in mine waste rich in these heavy metals which eventually find their way into surrounding environments Schippers et al 2007). Copper and Zn are micronutrients of plants but at high concentrations, they become phytotoxic (Yruela et al 2000;Nicholls and Mal 2003). Nickel may be essential for higher plants including potatoes (Solanum tuberosum), soybean (Glycine max L), cowpeas (Vigna unguiculata L. Walp), tomato (Lycopersicon esculentum L.) and barley (Hordeum vulgare L.) where it has been shown to prevent urea accumulation, but its metabolic role is yet to be established in many plants (Brown et al 1987;Bai et al 2006;Kabata-Pendias and Mukherjee 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even at low concentrations (Cu ++ /PS II reaction center <230), Cu significantly inhibited F v and oxygen evolution without any change in the protein composition. However, at a higher Cu concentration in the medium (Cu ++ /PS II reaction center > 1400), the OEC proteins (3 3,24 and 17 KDa) were removed (Yruela et al, 2000).…”
Section: B Copper (Cu)mentioning
confidence: 99%